Tinjauan Fatwa DSN MUI Terhadap Penyelesaian Pembiayaan Murābaḥah Bermasalah (Studi Kasus di Bank Pembiayaan Rakyat Syariah Dana Amanah Surakarta) - Mujahidin Yunani; M. Usman (Rayah Al-Islam, 2021)
Murābaḥah is one of the most popular financing for Sharia Financial Institutions. Likewise, at the BPRS Dana Amanah Surakarta, murābaḥah financing is what customers are most interested in, therefore, among other financing products the risk is also higher. In addition, many customers choose deferred payments. This deferred payment creates several risks, one of which is financing problems. Many customers who are deemed capable are still procrastinating in terms of payment of installment obligations, this is what causes losses for the BPRS, where the more customers delay payment, the higher the level of Non Performing Financing (NPF) in a bank, causing the bank's condition to not healthy. Then the problem that will be raised in this study is how to solve the problematic murābaḥah financing in the BPRS Dana Amanah Surakarta and how the view of the fatwa DSN MUI towards the practice of solving the problematic murābaḥah financing in the BPRS Dana Amanah Surakarta. This study uses field research methods, with a descriptive qualitative approach. The data sources used are primary data and secondary data, with data collection methods through interviews with informants and documentation and then analyzed with qualitative descriptive methods. From the results of this study, it can be concluded that: (1) The steps for solving problematic murābaḥah financing at BPRS Dana Amanah Surakarta include billing, rescheduling, restructuring, customers selling their own goods, execution of collateral, AYDA and judicial channels. (2) The mechanism for the settlement of murābaḥah financing at BPRS Dana Amanah Surakarta is in accordance with the MUI DSN Fatwa and POJK No. 29/POJK.03/2019, except for the Fatwa DSN MUI No. 47 / DSN-MUI / II / 2005 on the provisions of point 5 regarding exemption for customers who are truly unable to pay off their financing payments, because in its implementation the BPRS Dana Amanah Surakarta implementing the final solution of problematic murābaḥah financing by way of settlement through the judiciary, if the BPRS performs debt relief, only the write-off records are written off, not the write-offs. Even though it has been written off, there is still a billing.